THE EFFECT OF METHYLPREDNISOLONE VERSUS DEXAMETHASONE IN INCREASING THE DIABETOGENIC EFFECT OF SARS-CoV-2 INFECTION AND THE DEVELOPEMENT OF NEW-ONSET DIABETES MELLITUS - Srbinoska Bogatinoska, Milena; Popovska, Lidija; Prosheva, Tatjana; Bitoska, Iskra; Vidinic, Ivan; Vavlukis, Marija; Milenkovski, Marijan (Journal of Morphological Sciences; Vol 5 No 1 (2022): JMS, 2022)
SARS-CoV-2 causes predominantly lung disease, but by way of binding to the angiotensin-converting enzyme 2 (ACE2) receptors,it can attack key metabolic organs and may lead to alterations of glucose metabolism. The aim of the study was to examine the effect of methylprednisolone compared with dexamethasone on the glycaemic control as well as the development of new-onset diabetes in patients who were hospitalized due toCOVID-19 pneumonia. We reviewed the records of 203 consecutive patients who were hospitalized with a clinical presentation of COVID-19 pneumonia in the modular hospital at the University Clinic for Infectious Diseases and Febrile Conditions in Skopje, from December 2020until May 2021. We identified 65 patients with diabetes (32,0%), 49 patients (75%) of whichwith pre-existing diabetes, and 16 (25%) with newly diagnosed diabetes. Impaired glycoregulation was recorded in 19,2% of patients, of whom 5,5% did not receive any corticosteroid-therapy, 22,4% were treated with methylprednisolone â€“ pulse doses,and 21,4% were treated with dexamethasone. Patients with diabetes had a 1,9 times (CI 0,9-3,9) higher mortality rate than non-diabetic patients. We suggest that, if corticosteroid therapy is necessary during the treatment of COVID-19 pneumonia, it is safer to administer dexamethasone than methylprednisolone, especially in patients who have pre-existingdiabetes or are at risk ofdeveloping diabetes. Deterioration of glycoregulation and the need to replace oral antidiabetic therapy with insulin are common. New-onset diabetes often persists even after recovering from Covid-19. Keywords : SARS-CoV-2, Covid-19, pneumonia, corticosteroid therapy, glycoregulation, diabetes mellitus.   https://doi.org/10.55302/JMS2251103sb